Short-term movement and retreat sites of Leptodactylus labyrinthicus (Anura : Leptodactylidae) during the breeding season: A spool-and-line tracking study - Tozetti, A. M.; Toledo, L. F. (Soc Study Amphibians Reptiles, 2005)
Capture/recapture studies significantly increase our knowledge of the natural history of anuran amphibians. Many different methods have been employed in these studies, but a number of new techniques still require experimental validation. During two reproductive seasons in a Cerrado remnant in southeastern Brazil, we investigated the movement patterns and habitat use of the pepper frog, Leptodactylus labyrinthicus, using a spool-and-line device. This low-cost device did not appear to interfere with the activities of the frogs and allowed for constant monitoring, showing precise routes of movement and great predictability of relocations. Both sexes were active at night. During the day, males and females made use of retreat sites under vegetation or in burrows constructed by small- and medium-sized mammals. Males and females did not use standardized routes; there were no significant differences between their movements, and movements were not correlated with body size or environmental conditions. Individuals are able to move further than 100 m per day, a characteristic that may enable this species to colonize or recolonize open areas.